The Contribution of the APEC Forum to Resolving Healthcare Issues - SOKOVA, Evgenia A.; GNATIK, Yekaterina N. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The paper is dedicated to the research of the ‘Asia-Pacific Economic Cooperation’ international forum’s activity in the area of healthcare. The authors outline the main projects of the participating economies aimed at strengthening cooperation on various issues of public health (pharmacy, infectious disease dissemination, legislation harmonization, standard development). The paper contains the analysis of the forum’s performance efficiency based on the features of its running.
Keywords: international medical law; right to health; international cooperation; APEC; European Union; healthcare